Active landscapes of Iberia - Pedro Galve, Jorge (2020)
The recent geodynamic evolution of Iberia is recorded in its topography. Geomorphic markers and their dating; morphometric indices estimated through cutting-edge DEM analysis techniques; and the link of all this data with results of geophysical studies allow discussing why Iberia displays the highest average elevation in Europe and shows a particular topography with such diversity of landscapes. For example, the region of the Iberian (or Hesperian) Massif, the western sector of Iberia, shows an anomalous average elevation without a satisfactory explanation. On the other hand, different explanations about the recent evolution of the Alpine mountain ranges of the eastern sector of Iberia have come to light after macroscale landscape analyses. This is strengthening the debate on the driving force behind the actual topography of the Pyrenees, Cantabrian Mountains, Iberian Chain and Betics.